'Dead-tired' – a novel MDT approach to fatigue management for patients with advanced disease. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Bowler, Emily; Malik, Farida
Abstract : Introduction: Fatigue is a common and distressing symptom for patients with malignant and non-malignant disease.1 The importance of specific training programmes for managing fatigue have been cited.2 The authors describe an innovative multi-professional fatigue clinic for patients with advanced disease. Methods: A palliative care occupational therapist/physiotherapist-led fatigue clinic was developed in the day therapy unit in St Wilfrid's Hospice, Eastbourne. The clinic involves 4 weekly sessions; topics include breathing techniques, graded exercise, energy conservation (pacing, prioritising), energy restoration (nutrition, sleep, relaxation) and a complimentary therapy led session. Data collected as part of the service included patient self-reported fatigue (brief fatigue inventory (BFI)) collected at start, 4 weeks & 5-week follow-up) and demographics. Patients also completed a fatigue diary and service evaluation. Descriptive statistics were used to describe service findings. A paired t test was used to describe difference in global BFI score at start and at 4 weeks. Results: Twenty-seven patients were referred to the clinic (25 internal hospice referrals) 18 started the service. Nine patients were unable to start (seven unwell, one died, one declined). Results are available on 17 patients (mean age 64.6 years (SD 10.7), 71% female, ) 16/17 had a cancer diagnosis (5/16 had breast cancer, 5/16 colo-rectal cancer). Mean global BFI at start=69.1 (range 48–85) and at 4 weeks=54.9 (range 40–72). Mean improvement in global BFI score=14.2, t=3.3, p=0.02, n=10. Patients positively evaluated the service. Further data for 5-week follow-up, to follow. Conclusion: Findings suggest the fatigue clinic appears beneficial in managing patient fatigue. Early referral is recommended, so patients are seen before their disease has progressed too far.